Did student ratings of instruction achive the purpose for which they were intended? a consequential validity investigation for administrative purposes - Safavi, Seyedeh Azadeh; Abu Bakar, Kamariah; Ahmad Tarmizi, Rohani; Alwi, Nor Hayati (Centre for Promoting Ideas, 2013)
Student ratings of instruction are widely practiced in universities. They have been the subject of several validity studies with much of the research focusing on traditional evidence of validity. However, fewer studies have been devoted to consequential validity of student ratings. This study examined consequential validity of student ratings by investigating evidence on ‘consequences’ and ‘utility’ of student ratings regarding the use for administrative purposes. The population comprised administrators from 15 faculties of a major research university. The data collected were analyzed using descriptive statistics, multiple group analysis, and Pearson’s product moment correlation analysis. The paper's uncovering of administrators’ responsiveness to student ratings, and the identification of influenced dimensions of administrative practices, can make useful contributions to the literature on student ratings. The findings improved and supported validity of the student ratings and provided the university with reliable evidence for justifying the use of student ratings for administrative purposes. Also, the findings showed that higher education administrators regarded ‘instructor’s efforts in student learning enhancement’ as the most useful type of information provided by students.